Ascidiacea (Chordata, Tunicata) from Uruguay (SW Atlantic): Checklist and zoogeographic considerations - Scarabino, Fabrizio (2018)
The diversity of ascidians from the Southwestern Atlantic between 30°S and 40°S (southern Brazil, Uruguay and northern Argentina) remains as one of the poorest known of the West Atlantic. The objective of this work is to compile, analyze and discuss all published records of ascidians from Uruguay. They show the historical relevance of the studies performed by Herdman, Monniot F. and Monniot C. on ascidians collected at deep-sea stations by the HMS Challenger and the RV Atlantis II in the Argentine Basin. Total literature records include 38 ascidian species which are enumerated here for the first time. On the basis of the current knowledge, the ascidian fauna of Uruguayan waters encompasses: a) shallow-water species with temperate distribution (3 spp.); b) shelf and deep-sea species with Antarctic and Sub-Antarctic distribution (13 spp.); c) deep-sea species until now only collected off Río de La Plata (11 spp.); d) deep-sea species displaying a wide distribution (11 spp.). Only nine species have been recorded for the continental shelf; the remaining species were collected either from the slope (21) or the abyssal plain (5) or both deep-sea zones (3). Future research should be directed to record coastline and shelf species, assess the presence of exotic elements, and re-describe enigmatic species first described by Herdman (1882, 1886).